Distribution of protectin (CD59), a complement membrane attack inhibitor, in normal human tissues. - Meri, S; Waldmann, H; Lachmann, P (1991)
Protectin (CD59) is a recently discovered 18-20 kDa glycoprotein that effectively inhibits lysis by the membrane attack complex of the homologous complement system. This glycoprotein is widely distributed on the membranes of human blood cells (erythrocytes and leukocytes). By using immunofluorescence microscopy, protectin was observed in vascular endothelia throughout the body and in extravascular tissues. Cells expressing protectin were also found in ductal epithelia of pancreatic, biliary, and salivary systems, bronchi, and kidney collecting ducts. Furthermore, protectin was expressed in the epidermis and in the syncytiotrophoblast of placenta. The expression of protectin in endothelia, in various epithelial cells, and in placenta presumably protects autologous tissues and the fetoplacental unit from complement-mediated damage.